The effects of a blended learning model on the physical fitness of Chinese university students: a cluster randomized controlled trial in basketball education - Wang, Chen; Yuan, Yubin; Ji, Xueyan (BioMed Central Ltd, 2024)
Objective: The university period is a critical stage of personal development, and improving the physical fitness of university students is crucial to their academic performance, quality of life, and future. However, in recent years, the physical fitness level of Chinese university students has shown a decreasing trend. This study aimed to investigate the effects of a blended learning model on the physical fitness of Chinese university students through a 16-week intervention. Methods: A total of 78 first-year students from a public university in Henan Province were recruited for this study via a cluster randomized controlled trial (CRCT) design. The participants were divided into an experimental group (blended learning) and a control group (traditional learning). The intervention lasted for 16 weeks, and physical fitness indices such as body mass index (BMI), lung capacity, sit and reach, pull-ups/sit-ups, standing long jumps, 50-meter runs, and 1000/800-meter runs were measured before and after the intervention. Statistical analyses were conducted via generalized estimating equation (GEE) modeling, with the significance level set at P < 0.05. Results: Both learning models significantly improved students’ physical fitness after 16 weeks. However, the blended learning model resulted in more significant improvements in lung capacity, sit and reach, pull-ups/sit-ups, standing long jumps, and 50-meter runs (P < 0.05). No significant differences were found between the two groups in terms of BMI or 1000/800-meter run. Conclusions: The 16-week blended learning model effectively promoted physical fitness among university students, especially in terms of their lung capacity, flexibility, strength and speed.